A Bibliometric Mapping of Open Educational Resources - Zancanaro, Airton; Todesco, José Leomar; Ramos, Fernando (International Review of Research in Open and Distributed Learning, 2015)
Open educational resources (OER) is a topic that has aroused increasing interest by researchers as a powerful contribution to improve the educational system quality and openness, both in face to face and distance education. The goal of this research is to map publications related to OER, dating from 2002 to 2013, and available through the Web of Science and Scopus scientific databases as well as in the OER Knowledge Cloud open repository. Data were used to explore relevant aspects related to the scientific production in OER, such as: (i) number of publications per year; (ii) most cited publications; (iii) authors with higher number of publications; (iv) institutions and countries with more publications and (v) most referenced bibliography by the authors. The analysis has included 544 papers, written by 843 authors, from 338 institutions, from 61 different countries. Moreover, the analysis has included the publications referenced and the author’s keywords, considering 6,355 different publications and 929 different keywords. Besides presenting a bibliographic mapping of the research on OER, this paper also intends to contribute to consolidate the idea that OER is a promising field for researchers, in line with the spreading of the Open movement.